Comparison of Two-Dimensional and Three-Dimensional Radiographs Using Clinically Relevant Parameters - Julia C. Schmidt; Claudia-Julie Gutekunst; Dorothea Dagassan-Berndt; Patrick R. Schmidlin; Clemens Walter (MDPI AG, 2019)
This work compared the assessment of clinically relevant parameters by two-dimensional, that is, full-mouth intraoral radiograph (I-O) and panoramic radiograph (OPT), and three-dimensional, that is, cone beam computed tomography (CBCT), imaging methods. Different radiographic images (CBCT, I-O and OPT) were available for a 53-year-old female patient with dental and periodontal problems. A total of 14 dental and periodontal parameters were assessed by two independent examiners and compared among the three radiographic imaging modalities. For 10 parameters (71%), the CBCT images were superior to both I-O and OPT images. In contrast, CBCT demonstrated an inferior performance compared to I-O and OPT in the assessment of caries and dental restorations. Compared to OPT, I-O provided more clinically relevant findings for 10 out of 14 parameters (71%). Agreement between I-O and OPT was found with respect to dehiscence, fenestration, the number of bone walls and the root canal cross-section. Differences between the radiographic images were more likely to be detected when maxillary teeth rather than mandibular teeth were assessed with regard to furcation involvement, root proximity and root fusion.